Pengembangan Media Pembelajaran Panasia (Peta Flora Fauna di Indonesia) pada Materi IPS Kelas V SD - Saifudin, Mochamad Zainal; Kurniawati, Rikke; Murni, Arie Widya; Wardono, Mohammad Setyo; Yasin, Fajar Nur; Jannah, Novaria Lailatul (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
This research aims to improve student learning achievement as an effort to achieve competency through the development of learning media in social science material at MINU KH. Mukmin Sidoarjo in grade V and aims to design and develop Panasia (Map of Flora and Fauna in Indonesia) learning media in social science material for grade V at MINU KH. Mukmin Sidoarjo. The type of this research is development research in the form of a 4-D model which is carried out through 4 stages, namely defining, designing, developing and disseminating, but the researcher did not reach the fourth stage because there is no distribution, but it is implemented in a school. The object of this research is grade V students in social science material with the aim of optimizing learning for teachers and students at MINU KH. Mukmin Sidoarjo. The results of this research show that Panasia learning media has a very big influence on the student learning process as seen from the validation results of media experts and material experts. Media expert validation was 84% ​​and material expert validation was 91%, as well as the product trials carried out by researcher at schools from the teacher response questionnaire results was 84% ​​and students response questionnaire results were 86.6%. The results of this research show that Panasia learning media is very suitable for use in supporting the learning system in schools in order to make it will be better.